PENGEMBANGAN MODEL PEMBELAJARAN PASSING BOLABASKET MENGGUNAKAN KARTU TUGAS PADA PEMBELAJARAN PENJASORKES BAGI SISWA KELAS VIII DI SMP NEGERI 1 AJIBARANG KABUPATEN BANYUMAS TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improve and produce the result namely the teaching method passingBasketball uses the card task in studiying of sport lesson for Yunior High School students of sport education.The improving procedure that used by some steps ; 1) To analyze the result that will be improved, 2) Toimprove the first result (the teaching method passing Basketball uses the card task), 3) The expert validationusing one sportsman and two teachers, 4) A try out the field by a small group (34 students) and a big group (64students), 5) To resive and improve the result. The using instrument is to know the result quality by 1 )Quesionnaires from a sportman, 2) The data of the artery beat getting before and after studying, 3) Theresponse quesionnaire of psychomotori, cognitive, and affective of the student by questionnaire, 4) Themonitoring of the base tecnique effective that is used in the result namely chest pass, bounce pass, and verheadpass. The Using conslusion of the teaching result of Passing Basketball uses the card task in studying of sportlesson from Yunior Haigh School student gives the influence of teh physic intensity of student, can solve tehproblem, it i teh limitedness of instrument and infrastucture at school , can solve teh limitedness of the teachingtime and give the coordination aexperience of complex gesture from the student.